2019
DOI: 10.1016/j.neuroscience.2018.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Microglia and Neonatal Brain Injury

Abstract: Microglial cells are now recognized as the "gate-keepers" of healthy brain microenvironment with their disrupted functions adversely affecting neurovascular integrity, neuronal homeostasis, and network connectivity. The perception that these cells are purely toxic under neurodegenerative conditions has been challenged by a continuously increasing understanding of their complexity, the existence of a broad array of microglial phenotypes, and their ability to rapidly change in a context-dependent manner to atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(82 citation statements)
references
References 129 publications
(168 reference statements)
5
77
0
Order By: Relevance
“…In addition, immediate microglial activation occurs following HI and mediates brain injury (Hagberg et al, 2015;Shao et al, 2017). Activated microglia mainly contributes to neuro-inflammation and releases inflammatory mediators including tumor necrosis factor-α and interleukin-1β, leading to neuronal dead and excitotoxic injury (Mallard et al, 2018). Pharmacologic inhibition of microglial activation suppresses HI-induced neuronal apoptosis (Arvin et al, 2002;Li et al, 2014).…”
Section: Neuronal Cell Death and Neuro-inflammation Were Attenuated Fmentioning
confidence: 99%
“…In addition, immediate microglial activation occurs following HI and mediates brain injury (Hagberg et al, 2015;Shao et al, 2017). Activated microglia mainly contributes to neuro-inflammation and releases inflammatory mediators including tumor necrosis factor-α and interleukin-1β, leading to neuronal dead and excitotoxic injury (Mallard et al, 2018). Pharmacologic inhibition of microglial activation suppresses HI-induced neuronal apoptosis (Arvin et al, 2002;Li et al, 2014).…”
Section: Neuronal Cell Death and Neuro-inflammation Were Attenuated Fmentioning
confidence: 99%
“…During recent years the role that microglia plays in disorders of the CNS has been thoroughly studied (Crews et al 2017;Salter and Stevens 2017). Microglia has been shown to be involved in different processes such as regulation of embryonic vasculogenesis, secretion of trophic factors, immuno-surveillance, oligodendrogenesis and neurogenesis (Mallard et al 2018). It has been observed that neuroinflamation due to hypoxia-ischemia plays a key and deleterious role in this event (Galinsky et al 2018).…”
Section: Neuroinflammation and Astrogliosis Induced By Ai Is Partiallmentioning
confidence: 99%
“…1,2 Microglial cells are known with their role in synapse formation and blood-brain barrier development in the fetal brain and their contribution to establishing network connectivity during postnatal brain development. [2][3][4] The focus on different morphologic types of microglia and their role in embryonic vasculogenesis, neurogenesis, and building neuronal network during brain development gives another glimpse of hope in bridging the knowledge gap between normoxic and hypoxic fetal brain development, particularly in the understanding of the long-term neurodevelopmental outcome in survivors with congenital heart disease. [3][4][5][6] In this issue of the Journal, Lawrence and colleagues 7 from Children's Hospital of Philadelphia report that prenatal hypoxemia alters microglial morphology in experiments that used an assembly, an ''artificial womb.''…”
Section: Lok Sinha MD Nobuyuki Ishibashi Md and Can Yerebakan Mdmentioning
confidence: 99%